Role of the Epipapillary Membrane in Maculopathy Associated with Cavitary Optic Disc Anomalies: Morphology, Surgical Outcomes, and Histopathology. (8th May 2018) - Tanaka, Atsushi; Saito, Wataru; Kase, Satoru; Ishijima, Kan; Noda, Kousuke; Ishida, Susumu
Abstract : Purpose . To evaluate the surgical outcomes of pars plana vitrectomy (PPV) with epipapillary membrane removal in patients with maculopathy associated with cavitary optic disc anomalies. Methods . Eight patients (8 eyes) with cavitary optic disc anomaly-associated maculopathy who underwent PPV with epipapillary membrane removal were retrospectively reviewed. The best-corrected visual acuity (BCVA) and macular and papillary morphologies using enhanced depth imaging optical coherence tomography (EDI-OCT) were evaluated before and after treatment. Immunohistochemistry for an intraoperatively excised epipapillary membrane tissue was also performed. Results . Before surgery, EDI-OCT revealed that epipapillary membrane was observed in all patients. Retinoschisis was resolved with no recurrence in all patients following vitrectomy regardless of a disease type or the presence or absence of preoperative posterior vitreous detachment. The mean final BCVA and central retinal thickness significantly improved compared with pretreatment values (P = 0.008 and 0.004, resp.). Immunoreactivity for S100 protein and glial fibrillary acidic protein, markers of astrocytes, was positive in the resected membrane tissues. Conclusions . These results suggest that epipapillary membrane is involved in the pathogenesis of some patients with cavitary optic disc anomaly-associated maculopathy as well as posterior hyaloid membrane. PPV with epipapillary membrane removal may be a useful treatment option for this maculopathy. This trial is registered withUMIN000011123 .